Second language research methods - Seliger, Herbert W. (Oxford Univ. Press, 2000)
This book provides a clear, comprehensive, and authoritative guide to research methods in second language and bilingualism. Based on a set four research parameters, it discusses the development of research questions and hypotheses, naturalistic and experimental research instruments.